Chemical stability of copper solvent extraction reagents type hidroxioxime under different operational conditions - Navarro, Patricio (2009)
The chemical stability of two reagent extractants for copper, one without modifier (LIX 860N-IC) and the other containing a low viscosity modifier was studied. During 103 days the organic solutions (35% v/v in Shellsol 2046 AR diluent) were contacted with aqueous solutions containing 35 g/l copper, 180 and 290 g/l of sulfuric acid, respectively, working at two different conditions of temperature (25 and 45 °C). For both cases a negative effect of increased temperature and concentration of sulfuric acid was found. This effect begins to display from the day 50. For the aldoxime without modifier the extraction isotherms and maximum load were deteriorate and the formation of aldehyde in all cases from day 53. For the aldoxime with low viscosity modifier was possible to see a slight deterioration in the metallurgical performance in relation with the initial condition from the day 53. For more severe condition 45 °C and 290 g/l the extraction isotherm showed a slight drop, the maximum load decreased by approximately 25%.